Improving applied mathematics education - Buckmire, Ron, 1968-; Libertini, Jessica M., 1977- (Cham : Springer, 2021)
This book presents various contemporary topics in applied mathematics education and addresses both interested undergraduate instructors and STEM education researchers. The diverse set of topics of this edited volume range from analyzing the demographics of the United States mathematics community, discussing the teaching of calculus using modern tools, engaging students to use applied mathematics to learn about and solve problems of global significance, developing a general education course for humanities and social sciences students that features applications of mathematics, and describing local mathematical modeling competitions and their use in providing authentic experiences for students in applying mathematics to real world situations. The authors represent diversity along multiple dimensions of difference: race, gender, institutional affiliation, and professional experience.
5.1 Introductory Modelling Workshop for Students -- 5.2 Other Possible Workshops -- 6 Student and Faculty Feedback -- 6.1 Student Feedback -- 6.1.1 Student Motivation: Why Do You Want to Attend the Competition? -- 6.1.2 Student Expectation: What Do You Expect from This Competition? -- 6.1.3 Student Reflections After the Competition -- 6.2 Faculty Feedback -- 6.2.1 SVMMC Faculty Feedback -- 6.2.2 SUTD-MMC Faculty Feedback -- 7 Conclusions -- References
Keywords: Mathematics -- Study and teaching; Mathematics -- Study and teaching; Electronic books; Electronic books